Comparison of oxcarbazepine efficacy and MHD concentrations relative to age and BMI: Associations among ABCB1, ABCC2, UGT2B7, and SCN2A polymorphisms. Issue 12 (March 2019) - Yang, Xue; Yan, Yuanliang; Fang, Shu; Zeng, Shuangshuang; Ma, Hongying; Qian, Long; Chen, Xi; Wei, Jie; Gong, Zhicheng; Xu, Zhijie
Abstract : Abstract: Genetic polymorphisms are related to the concentration and efficacy of oxcarbazepine (OXC). 10-Hydroxycarbazepine (MHD) is the major pharmacologically active metabolite of OXC, and it exerts an antiepileptic effect. This study aimed to explore the connection between the MHD concentration and genes such as ATP-binding cassette B1 (ABCB1), ATP-binding cassette C2 (ABCC2), UDP-glucuronosyltransferase-2B7 and sodium voltage-gated channel alpha subunit 2 (SCN2A), which participate in the antiepileptic function of OXC. Total 218 Chinese epileptic patients, were stratified into different groups according to their age, body mass index (BMI) and OXC efficacy. The genotypes of 7 single nucleotide polymorphisms in all subjects were determined by polymerase chain reaction-improved multiple ligase detection reaction assay. The MHD plasma concentration was detected by high-performance liquid chromatography and then standardized through dosage and body weight. In general, the ABCC2 rs2273697 mutant ( P  = .026) required a significantly higher standardized MHD concentration. For age groups, carriers of the ABCC2 rs2273697 mutant showed a significantly higher standardized MHD concentration than noncarriers in the juvenile group ( P  = .033). In terms of BMI, a significantly higher standardized MHD concentration was found in the ABCB1 rs2032582 mutant of the normal weight group ( P  = .026). The SCN2A rs17183814 mutant required a significantly higher OXC maintenance ( P  = .014) in the low-weight group, while lower OXC maintenance dose ( P  = .044) and higher standardized MHD concentration ( P  = .007) in the overweight group. The ABCC2 rs2273697 polymorphism was significantly associated with MHD plasma concentration in the whole patient cohort and in patients stratified by different ages, this finding provides potential theoretical guidance for the rational and safe clinical use of OXC. Abstract : Supplemental Digital Content is available in the text